DAYA DUKUNG FISIK DAN PERSEPSI PENGUNJUNG PANTAI LUBANG BUAYA DI NEGERI MORELLA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Latukau, Syarifa; Latupapua, Yosevita; Seipalla, Billy (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The aim of this research is to determine the physical carrying capacity and perceptions of visitors at Lubang Buaya Beach, Leihitu District, Central Maluku Regency. This research uses direct observation and interviews based on research questionnaires to collect data at Lubang Buaya Beach. The research results show that the physical carrying capacity values ​​for picnicking and swimming are 1,302 and 604 visitors/day. If we look at the number of visits on big holidays and weekends of 200 people/day, it is still below the calculated physical carrying capacity value. Tourist perceptions are based on the classification of respondents' attitudes (Presntasi) on the question variable of tourist perceptions (respondents) towards the Lubang Buaya Beach tourist attraction, some tourists stated that they were satisfied with the attractions of the tourist attraction, satisfied with carrying out activities while at Lubang Buaya Beach, while for the amenities and accessibility of the object Lubang Buaya Beach tourism most tourists expressed satisfaction.